2021
DOI: 10.1002/cpt.2202
|View full text |Cite
|
Sign up to set email alerts
|

From Therapeutic Drug Monitoring to Model‐Informed Precision Dosing for Antibiotics

Abstract: (ISAP), the PK/PD study group of the European Society of Clinical Microbiology, Infectious Diseases (EPASG) Therapeutic drug monitoring (TDM) and model-informed precision dosing (MIPD) have evolved as important tools to inform rational dosing of antibiotics in individual patients with infections. In particular, critically ill patients display altered, highly variable pharmacokinetics and often suffer from infections caused by less susceptible bacteria. Consequently, TDM has been used to individualize dosing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
174
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(187 citation statements)
references
References 112 publications
4
174
0
9
Order By: Relevance
“…Still, none of these studies investigated a clinical primary endpoint, nor was the cost-effectiveness of an MIPD strategy evaluated. In adults, several retrospective or small clinical trials have suggested a clinical benefit from antibiotic TDM, with or without MIPD [186]. Recently, preliminary results of the TARGET trial, a large multicenter randomised controlled trial (RCT) in 10 German ICUs, failed to show a clinical benefit from TDM-guided dosing of piperacillin-tazobactam in critically ill adults [187].…”
Section: Discussionmentioning
confidence: 99%
“…Still, none of these studies investigated a clinical primary endpoint, nor was the cost-effectiveness of an MIPD strategy evaluated. In adults, several retrospective or small clinical trials have suggested a clinical benefit from antibiotic TDM, with or without MIPD [186]. Recently, preliminary results of the TARGET trial, a large multicenter randomised controlled trial (RCT) in 10 German ICUs, failed to show a clinical benefit from TDM-guided dosing of piperacillin-tazobactam in critically ill adults [187].…”
Section: Discussionmentioning
confidence: 99%
“…The main flaw of traditional TDM is the existence of a reference range of concentrations instead of one target concentration, which means that a clinician's decision making is driven by experience, rather than evidence-based facts (71,76). Moreover, samples should be taken from patients after steady state is achieved (77). One way to overcome the disadvantages of classical TDM is to use approaches that take into account the drug, disease, and patient characteristics, such as the model informed drug precision approach (MIPD) (78).…”
Section: Dose Individualisationmentioning
confidence: 99%
“…One way to overcome the disadvantages of classical TDM is to use approaches that take into account the drug, disease, and patient characteristics, such as the model informed drug precision approach (MIPD) (78). In this approach, TDM data, together with the individual patient's demographic, pharmacogenetic, clinical and therapy characteristics, are interpreted using the population model (31,77,79). Even before the administration of the first dose, the developed model can be used to calculate population parameters considering covariates for the specific patient and propose dosage regimen based on these estimates.…”
Section: Dose Individualisationmentioning
confidence: 99%
See 2 more Smart Citations